Clinical outcome after particle therapy for meningiomas of the skull base: toxicity and local control in patients treated with active rasterscanning - El-Shafie, Rami; Eitz, Kerstin Anne; Habermehl, Daniel; Kronsteiner, Dorothea; Rieken, Stefan; Bougatf, Nina; Jäkel, Oliver; Debus, Jürgen; Combs, Stephanie (Radiation oncology, 2018)
Meningiomas of the skull base account for 25-30% of all meningiomas. Due to the complex structure of the cranial base and its close proximity to critical structures, surgery is often associated with substantial morbidity. Treatment options include observation, aggressive surgical intervention, stereotactic or conventional radiotherapy.
Gesehen am 09.04.2018